A taxonomy of technological settings, with related strategies and performance levels - Miller, Alex (Strategic Management Journal, 1988)
In this study, businesses were categorized into six groups on the basis of their methods of production, rates of innovation, and product sophistication. Technology, strategy, and performance‐related variables were then used to successfully relate these categories to archetypes in three existing conceptual typologies. Although the strategies of the six groups differed significantly, their profitability levels did not.